Co-leadership and hotel management. The account systems USALI and BSC to improve effectiveness and efficiency. The portuguese case - Lamelas, J. P.; Filipe, J. (International Journal of Latest Trends in Finance and Economics Sciences, 2012)
In a very competitive, uncertain and very complex environment, it is supposed that changing from a single leader to a leadership team with complementary skills is an evolution that may highly contribute for motivating, to allow a good organizational environment and to get a more effective and efficient system in the organization. This research aims to verify whether or not there is a relationship between the model of co-leadership and the improvement of effectiveness and efficiency in the Portuguese hotel companies. For this purpose, we got answers for 1723 questionnaires, interviews were made, customers' satisfaction was tested, economic and financial performance was studied and specific case studies were made. In the study, the results confirm that the stronger the co-leadership is, the better the effectiveness and the efficiency are. “Co-leadership” and “GOP – Gross Operating Profit” variables are strongly correlated among themselves and with other important indicators of operational effectiveness such as “Organizational Environment”, “Work Motivation” and “Customers' Satisfaction”.